Image Colourization and Object Detection Using Convolutional Neural Networks - Kumar, K. Sree; Basu, Sourya; Shukla, Naveen Raj (International Journal of Psychosocial Rehabilitation, 2020)
Image colorization is the mechanism of proceeding with a gray scale image as input and delivering colorized image as output that personifies the acceptable colors and tones of the image input (for instance, a sky on a clear sunny day must be obviously “blue” – it can’t be colored “red” by the model). The approach we will use relies on deep learning. We will use a Convolutional Neural Network able enough of colorizing black and white images with results. We’ll also apply object detection using which we will be able to know not only what is in the image but also where an object resides.